Front Cover: Topological Sound Pumping of Zero‐Dimensional Bound States (Adv. Quantum Technol. 9/2020). Issue 9 (15th September 2020) - Gao, Penglin; Christensen, Johan
Abstract : A Majorana‐like bound state can be engineered in artificial acoustic lattices thanks to a Jackiw–Rossi vortex, which is the analog of a topological superconductor vortex. Such vortex is created by introducing a Kekulé texture to the man‐made lattice of rigid cylinders. In article number 2000065, Penglin Gao and Johan Christensen show how this binding mechanism can be well explained by a topological pumping process comprising adiabatic variations of the cylinder radii, which concentrates strong acoustic energy to the lattice center as shown in the cover image.